Sliding Scale Regular Human Insulin for Identifying Critically Ill Patients Who Require Intensive Insulin Therapy and for Glycemic Control in those with Mild to Moderate Hyperglycemia - Sarah V. Cogle; Susan E. Smith; George O. Maish III; Gayle Minard; Martin A. Croce; Roland N. Dickerson (Journal of Pharmacy and Nutrition Sciences, 2017)
Two sliding scale regular human insulin (RHI) algorithms (SSI) were retrospectively evaluated to identify those who develop severe hyperglycemia (blood glucose (BG) > 180 mg/dL) and for glycemic management of continuously-fed, critically ill trauma patients with mild to moderate hyperglycemia (BG 126 to 179 mg/dL). Assignment of low or high SSI was based upon anticipated severity of difficulty in glycemic control. BG was obtained every 3 to 6 hours. Target BG range was 70 to 149 mg/dL. Patients who were unable to achieve a BG < 150 mg/dL with SSI and who required a continuous intravenous RHI infusion were identified. Twenty-five of 121 patients (21%) failed SSI necessitating more intensive insulin therapy. The low and high intensity SSI groups exhibited a baseline BG of 123 + 33 mg/dL and 164 + 20 mg/dL (P = 0.001). Average BG for each group was 129 ± 14 mg/dL and 145 ± 21 mg/dL (P = 0.001). Each group spent 20 ± 4 and 16 ± 5 hours/day within the target BG range (P = 0.001), respectively. Mild hypoglycemia (BG 40 - 60 mg/dL) occurred in 11% and 7% of patients from each group (P = N.S.). Severe hypoglycemia (BG < 40 mg/dL) occurred in zero and two (5%) patients, respectively (P = N.S). SSI served as a useful technique to identify those requiring more intensive insulin therapy and was safe and efficacious for continuously-fed, critically ill trauma patients with mild to moderate hyperglycemia.